2014
DOI: 10.1117/1.jbo.19.12.126016
|View full text |Cite
|
Sign up to set email alerts
|

Combined lineage mapping and gene expression profiling of embryonic brain patterning using ultrashort pulse microscopy and image registration

Abstract: During embryogenesis, presumptive brain compartments are patterned by dynamic networks of gene expression. The spatiotemporal dynamics of these networks, however, have not been characterized with sufficient resolution for us to understand the regulatory logic resulting in morphogenetic cellular behaviors that give the brain its shape. We have developed a new, integrated approach using ultrashort pulse microscopy [a high-resolution, two-photon fluorescence (2PF)-optical coherence microscopy (OCM) platform using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
(57 reference statements)
1
7
0
Order By: Relevance
“…OCM has been combined with two-photon microscopy [217] to provide high-resolution registered images of brain patterning and morphogenesis in live zebrafish embryos. OCT has also been combined with photoacoustic tomography to image tissue optical scattering and absorption profiles simultaneously [218, 219].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…OCM has been combined with two-photon microscopy [217] to provide high-resolution registered images of brain patterning and morphogenesis in live zebrafish embryos. OCT has also been combined with photoacoustic tomography to image tissue optical scattering and absorption profiles simultaneously [218, 219].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The failure of the constriction to continue morphogenesis in the maintenance phase is due to aberrant cell behaviors in two groups of cells. By imaging a transgenic wnt1 reporter line (Gibbs et al, 2014b ) in the ace(fgf8a) background, we identified one group of cells that fails to maintain wnt1 expression in the posterior midbrain, and to subsequently coordinate the proper morphogenesis of the PML and boundary tegmentum, and another group that fails to suppress wnt1 expression in the dorsal part of r1 to correctly specify the cerebellar plate (Figures 2 , 3 ). This observation, based on identification of individual cells, supports previous reports of an isthmo/cerebellar-to-tectal transformation in molecular identity of the presumptive cerebellum that occurs with genetic reprogramming during the maintenance phase (Jászai et al, 2003 ; Gibbs, 2014 ), though with live imaging we observed that this reprogramming caused by a lack of fgf8a does not preclude the previous initiation of the morphogenesis of the MHB during the activation phase.…”
Section: Midbrain Hindbrain Domain Morphogenesis and Patterningmentioning
confidence: 99%
“…Generated two-photon excited fluorescence is collected in back-reflected geometry by the microscope objective and directed to photon-counting photomultiplier tubes for image rendering. In this configuration, our UPM system is point-scanning wherein images are rendered digitally pixel-by-pixel (Gibbs et al, 2014b ).…”
Section: New Tools For Addressing An Old Model Organizermentioning
confidence: 99%
See 1 more Smart Citation
“…OCT has been explored in many applications over the past decade, including ophthalmology, cardiovascular, oncology, and dermatology [28][29][30][31] as well as embryogenesis, angiogenesis, and tissue engineering. [32][33][34][35][36] Polarization-sensitive OCT (PS-OCT), 37,[38][39][40] as a functional extension of OCT, uses the information encoded in the polarization state of the recorded interference fringe intensity to provide additional contrast. In birefringent materials, a phase delay between the two orthogonally polarized wave components is caused by the difference of the refractive indices n o and n e of the ordinary and extraordinary wave Δn ¼ n o − n e , resulting in different phase velocities of both wave components.…”
Section: Introductionmentioning
confidence: 99%